2001
DOI: 10.1038/35055559
|View full text |Cite
|
Sign up to set email alerts
|

The gating mechanism of the large mechanosensitive channel MscL

Abstract: The mechanosensitive channel of large conductance, MscL, is a ubiquitous membrane-embedded valve involved in turgor regulation in bacteria. The crystal structure of MscL from Mycobacterium tuberculosis provides a starting point for analysing molecular mechanisms of tension-dependent channel gating. Here we develop structural models in which a cytoplasmic gate is formed by a bundle of five amino-terminal helices (S1), previously unresolved in the crystal structure. When membrane tension is applied, the transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
385
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(414 citation statements)
references
References 20 publications
26
385
3
Order By: Relevance
“…3 we display individual results for 15 Water Penetration Around Gly-34. Given the backbone flexibility of a Gly residue and its propensity to kink transmembrane helices (29)(30)(31), it was not surprising that helix kinking was observed in our simulations around Gly-34, the only Gly residue in the M2 TMD. The small size of the Gly side chain may allow for water access and hydrogen bonding with the backbone in the vicinity of the kink, thereby stabilizing it.…”
Section: Validation Of the Ensembles Of MD Conformations By Polarizationmentioning
confidence: 96%
“…3 we display individual results for 15 Water Penetration Around Gly-34. Given the backbone flexibility of a Gly residue and its propensity to kink transmembrane helices (29)(30)(31), it was not surprising that helix kinking was observed in our simulations around Gly-34, the only Gly residue in the M2 TMD. The small size of the Gly side chain may allow for water access and hydrogen bonding with the backbone in the vicinity of the kink, thereby stabilizing it.…”
Section: Validation Of the Ensembles Of MD Conformations By Polarizationmentioning
confidence: 96%
“…In order to evaluate to what extent our simulations reproduce the experimentally estimated MscL features, 7 we calculated the energy changes during the course of MscL opening and obtained an energy difference between closed and putative first-transition state. The obtained value, approximately 25 kcal/mol (42 k B T) in WT MscL, is comparable to the experimentally obtained value ca.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Purified MscL reconstituted into the lipid bilayer was found to retain its native mechanosensitive function, indicating that MscL activation is brought about exclusively by stress in the membrane and does not require any supporting proteins. 6,7 Patch-clamp experiments showed that MS channels are activated by tension in the membrane rather than by One of the ultimate goals of the study on mechanosensitive (MS) channels is to understand the biophysical mechanisms of how the MS channel protein senses forces and how the sensed force induces channel gating. The bacterial MS channel MscL is an ideal subject to reach this goal owing to its resolved 3D protein structure in the closed state on the atomic scale and large amounts of electrophysiological data on its gating kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations